The influence of pyrolysis temperature and dosage of shorea wood biochar produced on soil properties and sengon (Falcataria moluccana) seedling biomass - Riniarti, Melya; Hidayat, Wahyu; Prasetia, Hendra; Wijaya, Bangun Adi (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2025)
This study explores the effects of pyrolysis temperature of shorea wood biochar and its doses on the soil properties and biomass of Falcataria moluccana seedlings. The focus is optimizing pyrolysis temperatures (400°C and 600°C) and biochar doses (0%, 25%, and 50%) to enhance soil fertility and seedling biomass. Both pyrolysis temperature and biochar dose are critical factors that influence the soil properties, directly affecting its effectiveness as a soil amendment. The research was conducted as a controlled greenhouse experiment over 120 days; each treatment was replicated 15 times. We observed several soil chemical properties, including pH, cation exchange capacity (CEC), organic carbon (C-organic), total nitrogen (N-total), and total phosphorus (P-total). The growth parameters assessed included above ground biomass (AGB), below ground biomass (BGB), total biomass (TB), and root to shoot ratio (R:S). Data analysis involved one-way and two-way ANOVA. Results indicated that soil properties, particularly cation exchange capacity (CEC) and organic carbon content, were improved, thereby enhancing soil fertility. However, ANOVA indicated no statistically significant differences across treatments. Biochar significantly enhanced above-ground and below-ground biomass (AGB and BGB). Nevertheless, both pyrolysis temperature and biochar dose independently influenced biomass accumulation in F. moluccana seedlings. The highest increases were observed in the treatment with the highest pyrolysis temperature (600ᵒC) and the highest dose (50%), which led to an 85% increase in AGB and a 60% increase in BGB compared to the control. Based on the study, Shorea wood biochar, particularly when used at 600°C and 50% dose, significantly improves soil fertility and seedling growth, providing a promising approach for developing F. moluccana plantations.